Dynamic response-based isogeometric analysis of graphene platelets-reinforced functionally graded triply periodic minimal surface plates supported by Pasternak foundation - Ngoc-Tu Do; Huu Trong Dang; Trung Thanh Tran; Nguyen Vinh Du; Quoc Hoa Pham (Alexandria Engineering Journal)
Recent progress in additive manufacturing (AM) has transformed how complex bioinspired engineering structures are designed and produced. Nonetheless, these structures present substantial difficulties in mathematical modeling and computational analysis. The main goal of this paper is to develop an effective computational method to predict the dynamic response of graphene platelets (GPLs)-reinforced functionally graded triply periodic minimal surface (FG-TPMS) plates (referred to as GPLR-FG-TPMS plates) supported by PF. To achieve this, we employ TrSDT within the IGA framework for efficiency and accuracy. The study establishes advanced plate models by combining three sheet-based TPMS configurations with three porosity distributions and three GPL distribution variations through the plate thickness. Then, we consider the effects of geometrical parameters, material properties, and BCs on free vibration and the dynamic response of GPLR-FG-TPMS plates supported by PF. The findings greatly improve our understanding of the complex dynamic responses of GPLR-FG-TPMS plates, paving the way for applications in various fields in the future.